Gaya Komunikasi Selebgram Cherry Aprilina dalam Product Endorsement di Media Sosial Instagram - Ultari Ultari; Muhammad Fajri (Institut Nalanda, 2026)
Communication style is a way for individuals to communicate, interact, and behave with the aim of providing understanding to others, both verbally and non-verbally, conveyed by a communicator (sender) to a communicant (receiver) with the same purpose under certain conditions. The communication style of Instagram celebrity Cherry Aprilina in promoting products is carried out through agreements between the celebrity and business owners with the purpose of attracting customers or potential buyers by utilizing the services of a social media influencer. The main focus of this study is to answer the question: How is Cherry Aprilina’s communication style in product endorsement on Instagram social media. This study uses a descriptive qualitative research method. The data collection techniques include observation of Cherry Aprilina’s Instagram social media account and data analysis techniques in the form of words or statements, both written and spoken, that were systematically arranged and previously collected. Based on the findings observed from Cherry Aprilina’s Instagram account, there is evidence of interpersonal communication carried out by Cherry Aprilina in interacting with her followers on Instagram by applying Robert Norton’s communication style theory and Steward L. Tubbs & Sylvia’s communication style theory in product endorsement on social media. The communication style aspects most frequently used by Cherry Aprilina in promoting products are friendly, relaxed, animated expressive, attentive, and open. Meanwhile, the communication style categories proposed by Steward L. Tubbs & Sylvia that are reflected in her endorsements include The Controlling Style, The Equalitarian Style, and The Structuring Style